(3u+2)(7+u)=0

Simple and best practice solution for (3u+2)(7+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3u+2)(7+u)=0 equation:


Simplifying
(3u + 2)(7 + u) = 0

Reorder the terms:
(2 + 3u)(7 + u) = 0

Multiply (2 + 3u) * (7 + u)
(2(7 + u) + 3u * (7 + u)) = 0
((7 * 2 + u * 2) + 3u * (7 + u)) = 0
((14 + 2u) + 3u * (7 + u)) = 0
(14 + 2u + (7 * 3u + u * 3u)) = 0
(14 + 2u + (21u + 3u2)) = 0

Combine like terms: 2u + 21u = 23u
(14 + 23u + 3u2) = 0

Solving
14 + 23u + 3u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(7 + u)(2 + 3u) = 0

Subproblem 1

Set the factor '(7 + u)' equal to zero and attempt to solve: Simplifying 7 + u = 0 Solving 7 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + u = 0 + -7 Combine like terms: 7 + -7 = 0 0 + u = 0 + -7 u = 0 + -7 Combine like terms: 0 + -7 = -7 u = -7 Simplifying u = -7

Subproblem 2

Set the factor '(2 + 3u)' equal to zero and attempt to solve: Simplifying 2 + 3u = 0 Solving 2 + 3u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3u = 0 + -2 3u = 0 + -2 Combine like terms: 0 + -2 = -2 3u = -2 Divide each side by '3'. u = -0.6666666667 Simplifying u = -0.6666666667

Solution

u = {-7, -0.6666666667}

See similar equations:

| 7(y+6)+7y=9 | | 29x^2-24x-1.44=0 | | 4(x+1.48)=3x | | 5w+3w=20 | | 3y-5=12 | | .3x^2-.7x-4.0=0 | | 15+3m=7m+3 | | -2.29x^2-.24x-.0144=0 | | 32x+17y=196 | | S-1.8x=6.4 | | x^2+12x+100=y | | -6(6x+2)=4x-12 | | (2x-1)(x+3)=15 | | -4(t+1)-t-14=-5(t+5)+7 | | 3x(6+x)=24 | | 16-y=9 | | -4x+18=-2x+10 | | 5(x+2)+3(2x-3)=34 | | (7n/n-3)-4=15/n-3 | | -21p-5(6-6p)=4(p-2)-22 | | m/3-m/5=6 | | .29x^2-.24x-.0144=0 | | -3x^2+2x+5=x | | log(3x-17)=6 | | (5+z)(4z+1)=0 | | -7(v+4)+3v+7=8v+6 | | 4x=11.4285 | | 60+6x=70+4x | | a+(a+15)=265 | | 3e^2+5e= | | 14(v+4)-2v=4(3v+2)-16 | | 8x-7=19+15+7 |

Equations solver categories